TINJAUAN PRINSIP GOOD GOVERNANCE DAN PERSPEKTIF ISLAM DALAM OPERASIONAL LEMBAGA ZIS - Iswari, Putu Widhi; Rosyid, Maskur (Program Studi Manajemen Zakat dan Wakaf, 2020)
Abstract The Zakat and Alms (ZIS) Institution, as a non-profit organization are required to work professionally and proportionally. The complex of challenges in managing operational from other institution and also satisfaction as a target for all the stakeholders. Neglecting and ignoring of these challenges can stimulate the stagnation and less of trust from all the component in this institution. Therefore, alternative solutions are needed in order to minimize the negative possibilities. Through of this review of study, that using the perspective of principles Good Governance and Islamic perspectives, this paper intends to discuss both of the approaches as an input for the ZIS institution in Higher Education Institution within their operating system all the business process run efficient and effective. Nine principles of Good Governance within the Islamic principles are necessary to apply and to implement a good way. Abstrak Lembaga Zakat, Infak dan Sedekah (ZIS), sebagai lembaga non-profit, dituntut untuk bekerja secara profesional dan proporsional. Tuntutan semacam itu muncul dibarengi dengan tantangan zaman yang semakin kompleks. Menafikan tantangan berakibat pada kemandegan dan kehilangan kepercayaan dari stakeholders. Oleh karenanya, dibutuhkan solusi alternative dalam rangka menyiasati akibat negative tersebut. Melalui kajian pustaka, menggunakan perspektif prinsip-prinsip good governance dan prinsip Islam, tulisan ini hendak membincang kedua pendekatan tersebut sebagai alat baca pada tata kelola Lembaga ZIS pada perguruan tinggi. Sembilan prinsip good governance yang sejalan dengan prinsip Islam, menjadi mutlak untuk diterapkan pada tata kelola Lembaga ZIS di perguruan tinggi.